Recycled Tire Rubber in Additive Manufacturing: Selective Laser Sintering for Polymer-Ground Rubber Composites - Toncheva, Antoniya; Brison, Loïc; Dubois, Philippe; Laoutid, Fouad (Applied sciences, 2021)
Natural and synthetic rubber is gaining increased interest in various industrial applications and daily life sectors (automotive industry, acoustic and electrical isolators, adhesives, impermeable surfaces, and others) due to its remarkable physicomechanical properties, excellent durability, and abrasive resistance. These great characteristics are accompanied by some recycling difficulties of the final products, particularly originated from the tire waste rubber industry. In this study, recycled tire rubber was incorporated in polymer matrices using selective laser sintering as 3D printing technology. Two polymers were used-polyamide and thermoplastic polyurethane, for their rigid and elastomeric properties, respectively. Polymer composites containing various tire powder amounts, up to 40 wt.%, were prepared by physical blending. The final materials’ morphological characteristics, mechanical properties, and thermal stability were evaluated. The proposed ambitious additive manufacturing approach looked over also some of the major aspects to be considered during the 3D printing procedure. In addition, examples of printed prototypes with potential applications were also proposed revealing the potential of the recycled tire rubber-loaded composites.